2018
DOI: 10.1155/2018/3436429
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Multirobot Coverage Path Planning: Ideal-Shaped Spanning Tree

Abstract: The present paper attempts to find the optimal coverage path for multiple robots in a given area including obstacles. For single robot coverage path planning (CPP) problem, an improved ant colony optimization (ACO) algorithm is proposed to construct the best spanning tree and then obtain the optimal path, which contributes to minimizing the energy/time consumption. For the multirobot case, first the DARP (Divide Areas based on Robots Initial Positions) algorithm is utilized to divide the area into separate equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Chen et al [13] improved the accuracy of the spraying path by using an exponential mean Bézier curve and trajectory optimization based on ACO or GA, further enhancing the smooth path by optimizing the trajectory on the Bézier surface [241]. Gao et al [242] proposed an improved ACO algorithm to optimize the coverage performance by reducing the number of turns in multi-robot CPP in simulated 2D grid space. Ye et al [12] improved the algorithm by randomly calculating the transition probability and updating the pheromone besides the acceleration factor, improving the global searchability despite the randomness of the algorithm could induce failure.…”
Section: ) Swarm Intelligencementioning
confidence: 99%
“…Chen et al [13] improved the accuracy of the spraying path by using an exponential mean Bézier curve and trajectory optimization based on ACO or GA, further enhancing the smooth path by optimizing the trajectory on the Bézier surface [241]. Gao et al [242] proposed an improved ACO algorithm to optimize the coverage performance by reducing the number of turns in multi-robot CPP in simulated 2D grid space. Ye et al [12] improved the algorithm by randomly calculating the transition probability and updating the pheromone besides the acceleration factor, improving the global searchability despite the randomness of the algorithm could induce failure.…”
Section: ) Swarm Intelligencementioning
confidence: 99%
“…Similarly, Bouzid et al 23 applied rapidly exploring random tree star fixed nodes (RRT*-FN) combined with the genetic algorithm (GA) by assuming that the CPP issue emulates a vehicle routing problem (VRP). In addition, Gao et al 24 used spanning tree coverage (STC) with ant colony optimization (ACO). On the other hand, Ju et al 25 applied a distributed swarm control algorithm to show that the performance of the multi-UAV system is significantly superior to the single-UAV system.…”
Section: State Of the Artmentioning
confidence: 99%
“…If continuous broadband access between the agents is assumed, then all agents can obtain perfect localisation and sensor data from one another, and then the approaches can be based on some kind of global optimisation approach [12], with the capability to adapt to a timedependent environment [13]. Even though it has been shown that finding a globally optimal solution for the coverage maximisation of a multi-agent fleet is an NP-hard problem [14], it is possible to come quite close to this solution within real-time constraints [15], [16]; however, this requires intelligent strategies to guide the optimisation process (see more discussion on this subject later).…”
Section: Previous Studiesmentioning
confidence: 99%